Pension Reform Options in Chile : Some Tradeoffs - Santoro, Marika (IMF Working Papers; Working Paper ;, 2017)
In this paper, we study the macroeconomic impact of pension reform options in Chile, using a dynamic general equilibrium model. The main reform proposal considers raising contributions (employer side) and vehicle additional proceeds to individual accounts and to increase the support of solidarity pensions. We model increased contributions as a labor tax. We find the impact of this reform on GDP to be negative in the near to the medium run, with GDP declining by 0.5 percent by 2021, as a result of labor tax distortions which lead to a fall in labor supply, investment and to a loss in competitiveness. We also illustrate the main macroeconomics tradeoffs by analyzing alternative reforms, such as using revenues only to improve future pensions or a reform package funded by a mix of higher contributions and indirect taxes.